CO2 Gasification of Charcoals in the Context of Metallurgical Application. (May 2017) - Bui, Hau-Huu; Wang, Liang; Tran, Khanh-Quang; Skreiberg, Øyvind; Luengnaruemitchai, Apanee
Abstract: The CO2 gasification reactivity of Norwegian spruce charcoals from stem wood and its forest residue produced at different pressures was investigated in the present study. The gasification behavior was analyzed thermogravimetrically at different gasification temperatures of 800, 850 and 950 o C, followed by a kinetic modelling applying the random pore model (RPM) and overlapped grain model (OGM). It is found that gasification temperature has a considerable influence on the reactivity of charcoals. Higher carbonization pressures reduce the gasification reactivity of the produced charcoals towards CO2 . The employed kinetic models represents well the experimental data. The initial porosity computed through the OGM is found to depend on the carbonization pressure. The activation energy is found in the range of 210 to 230 kJ/mol, in line with the values reportedin the literature.